Development of a green combat armour from rame-Kevlar-polyester composite - Radif, Zainab Shakir; Ali, Aidy; Abdan, Khalina (Universiti Putra Malaysia Press, 2011)
This study was conducted for the development of the green protection garments. For this purpose, laminate composite material was developed from Kevlar 29-ramie-unsaturated polyester resin. The aim of this study was to develop a solid body armour that meets the specific requirements of ballistic resistance. This composite is subjected to high impact loading. The target was shot using gas gun machine that is supported by camera hardware to capture the projectile speed. In order to achieve the goal of the research, several experiments were conducted with the aim to estimate the ballistic limit, maximum energy absorption, composite failure mode, life time rupture, target geometry, and environmental effect. The results of these experiments indicated that the maximum ballistic limit validated at impact speed is in the range of 250 m/s to 656.8 m/s for the second protection level. The targets are improved in term of the impact response with the increase in the relative humidity, i.e. the range of 50% ± 20%, whereas, reduction of resistance results in the increase of temperature. The range of temperatures was between 20°C and 70°C. A limited delamination was generated under multiple shots. Targets geometry plays a major role in increasing the impact response. Hence, the results present a high resistant impact for pairs from the panels with total thickness arrived to 15 mm ± 3 mm. This body armour is one of the most economical armour products, in which common materials are used in its production, particularly to reduce the amount of Kevlar, and this could further lead to a decrease in its production cost. On the other hand, this armour meets the ballistic threats under 623 m/s of 15 mm ± 3 mm target thickness and 837.5 m/s of 25 mm ± 2.mm. Thus, the armour is equivalent to the third level of protective ballistic limits in the National Institute of Justice (NIJ) standards.